Optimization of Restaurant Tax Revenue in The Era of Covid-19 at The Regional Revenue Agency of Serang Regency - Intan Puspanita; Mulyanah Mulyanah; Asih Machfuzhoh; Farah Juliani (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims to analyze the optimization of restaurant tax collection, especially during the Covid-19 Pandemic, describe the inhibiting factors for collecting restaurant taxes, and find out what efforts are made by the Serang Regency Regional Revenue Agency in optimizing restaurant tax revenues. The method used in this research is descriptive with an inductive approach and data collection techniques using observation, interviews, and documentation. The results of this study are the realization of the Restaurant Tax in Serang Regency is still not optimal, especially in 2020 and 2021, it has not yet reached the target, and it is even said to be very far from reaching the target. The Covid-19 pandemic limits human activities which has an impact on the decline in the economy in Indonesia. Restaurants are one of the things that have been affected by Covid-19. The enactment of the PSBB has caused restaurants to experience a decrease in visitors and even restaurants have gone out of business. This has an impact on the decline in restaurant turnover so that the amount of tax paid also decreases.